Metabolic and kinematic effects of self-selected Q factor during bike fit - Disley, B. X.; Li, F.-X. (Research in Sports Medicine, 2014)
Correct bicycle fit is important, and kinematic instability must be addressed to reduce the risk of knee injury. A change in Q Factor (horizontal distance between crank arms) has been shown to decrease metabolic cost. The combined effect upon gross mechanical efficiency (GME) and knee variability is unclear, however; there is no known simple method to predict self-selected Q Factor (SSQ). The SSQ was hypothesized to provide the greatest GME and least variability at the knee. Ten trained cyclists completed bouts of submaximal cycling at a range of Q Factors. The effectiveness of hanging and stepping tasks as predictors of SSQ was also tested. Measured SSQ (142 mm) provided the best combination of GME and knee stability compared with other Q Factors, and could be accurately predicted using a simple hanging task. The SSQ has the potential to lower the risk of knee injury and provide increased efficiency whilst cycling.